2017
DOI: 10.1152/jn.00765.2016
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine induced converged synchronous gamma oscillations in the cortico-basal ganglia network of nonhuman primates

Abstract: -methyl-d-aspartate (NMDA) antagonists are widely used in anesthesia, pain management, and schizophrenia animal model studies, and recently as potential antidepressants. However, the mechanisms underlying their anesthetic, psychotic, cognitive, and emotional effects are still elusive. The basal ganglia (BG) integrate input from different cortical domains through their dopamine-modulated connections to achieve optimal behavior control. NMDA antagonists have been shown to induce gamma oscillations in human EEG r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 97 publications
3
26
0
Order By: Relevance
“…So at this point, little is known about single unit firing in the rapidly acting antidepressant ketamine, or the related NMDAR antagonists dizocilpine (MK-801) and phencyclidine (PCP). One finding that has been replicated a number of times in these studies, including for ketamine in vervet monkeys (Slovik et al 2017 ) and macaques (Skoblenick et al 2016 ), is that acute systemic administration of these three drugs, and in some cases infusion of them into local brain regions, tends to enhance gamma and high frequency oscillations (HFO) in a number of cortical and subcortical structures (Hakami et al 2009 ; Hunt et al 2008 , 2009 , 2010 ; Kealy et al 2017 ; Kjaerby et al 2017 ; Lee et al 2017 ; Matulewicz et al 2010 ; Nagy et al 2016 ; Nicolás et al 2011 ; Olszewski et al 2013 ; Wood et al 2012 ; Hunt et al 2006 ; Sullivan et al 2015 ; Maheshwari et al 2016 ). Of note, Hunt et al ( 2015 ) found that acute MK-801 not only increased the power of nucleus accumbens HFO but also produced a small increase in frequency, whereas the 5-HT2A antagonist clozapine and 5-HT1A agonist 8-OH-DPAT each counteracted this increase in frequency, suggesting functional opposition between these two 5-HT receptor subtypes in this effect (Hunt et al 2015 ).…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 70%
“…So at this point, little is known about single unit firing in the rapidly acting antidepressant ketamine, or the related NMDAR antagonists dizocilpine (MK-801) and phencyclidine (PCP). One finding that has been replicated a number of times in these studies, including for ketamine in vervet monkeys (Slovik et al 2017 ) and macaques (Skoblenick et al 2016 ), is that acute systemic administration of these three drugs, and in some cases infusion of them into local brain regions, tends to enhance gamma and high frequency oscillations (HFO) in a number of cortical and subcortical structures (Hakami et al 2009 ; Hunt et al 2008 , 2009 , 2010 ; Kealy et al 2017 ; Kjaerby et al 2017 ; Lee et al 2017 ; Matulewicz et al 2010 ; Nagy et al 2016 ; Nicolás et al 2011 ; Olszewski et al 2013 ; Wood et al 2012 ; Hunt et al 2006 ; Sullivan et al 2015 ; Maheshwari et al 2016 ). Of note, Hunt et al ( 2015 ) found that acute MK-801 not only increased the power of nucleus accumbens HFO but also produced a small increase in frequency, whereas the 5-HT2A antagonist clozapine and 5-HT1A agonist 8-OH-DPAT each counteracted this increase in frequency, suggesting functional opposition between these two 5-HT receptor subtypes in this effect (Hunt et al 2015 ).…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 70%
“…In our study, ketamine and DOI produced beta activity suppression occurring specifically in the inactive state and the suppression was also observable in the total data. Ketamine‐induced suppression of beta power appears stable across species as decreases have also been found in LFPs from mice (Lazarewicz et al., ), vervet monkeys (Slovik et al., ) and in human EEG (Knott et al., ) and MEG recordings (Muthukumaraswamy et al., ; Rivolta et al., ). Only one human study did not find any effect of ketamine on current densities in the beta band (de La Salle et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…However, as there was no antagonistic pattern of change for the induced background power after consecutive administration of SKF‐38393 and SCH‐23390, it cannot be ruled out that the observed broadband and low‐frequency effects might be due or at least be partially confounded by temporal changes related to anesthesia. Ketamine used for anesthesia in our study has been shown to alter neuronal oscillations in for instance lower frequencies (Blain‐Moraes et al ., ) or higher frequency ranges (Lazarewicz et al ., ; Slovik et al ., ). Ketamine anesthesia has been shown to reduce NMDA‐mediated synaptic input to inhibitory interneurons, as well as to pyramidal neurons, and by this contribute to the observed effects.…”
Section: Discussionmentioning
confidence: 97%